Malaria vaccines: identifying Plasmodium falciparum liver-stage targets - Longley, Rhea J.; Hill, Adrian V.; Spencer, Alexandra J. (Frontiers in Microbiology, 2015)
The development of a highly efficacious and durable vaccine for malaria remains a top priority for global health researchers. Despite the huge rise in recognition of malaria as a global health problem and the concurrent rise in funding over the past ten to fifteen years, malaria continues to remain a widespread burden. The evidence of increasing resistance to anti-malarial drugs and insecticides is a growing concern. Hence, an efficacious and durable preventative vaccine for malaria is urgently needed. Vaccines are one of the most cost-effective tools and have successfully been used in the prevention and control of many diseases, however the development of a vaccine for the Plasmodium parasite has proved difficult. Given the early success of whole sporozoite mosquito-bite delivered vaccination strategies, we know that a vaccine for malaria is an achievable goal, with sub-unit vaccines holding great promise as they are simple and cheap to both manufacture and deploy. However a major difficulty in development of sub-unit vaccines lies within choosing the appropriate antigenic target from the 5000 or so genes expressed by the parasite. Given the liver-stage of malaria represents a bottle-neck in the parasite’s life cycle, there is widespread agreement that a multi-component sub-unit malaria vaccine should preferably contain a liver-stage target. In this article we review progress in identifying and screening P. falciparum liver-stage targets for use in a malaria vaccine.